Η ΠΟΛΙΤΙΚΗ ΚΑΙ ΔΙΠΛΩΜΑΤΙΚΗ ΠΑΡΟΥΣΙΑ ΤΟΥ ΚΩΝΣΤΑΝΤΙΝΟΥ ΖΩΓΡΑΦΟΥ ΣΤΟΝ ΑΓΩΝΑ (1821-1827) - ΟΙΚΟΝΟΜΟΠΟΥΛΟΥ - ΣΙΜΟΠΟΥΛΟΥ ΜΑΡΙΕΤΤΑ (Μνήμων, 1972)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–>Δεν παρατίθεται περίληψη<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>